1994
DOI: 10.1172/jci117115
|View full text |Cite
|
Sign up to set email alerts
|

Extrathyroidal release of thyroid hormones from thyroglobulin by J774 mouse macrophages.

Abstract: Thyroglobulin appears in the circulation of vertebrates at species-specific concentrations. We have observed that the clearance of thyroglobulin from the circulation occurs in the liver by macrophages. Here we show that the thyroid hormones T3 and T4 were released by incubation of mouse macrophages (J774) with thyroglobulin. Thyroid hormone release was a fast process, with an initial rate of -20 pmol T4/mg per min and 0.6 pmolT3/mg per min, indicating that macrophages preferentially release T4. The bulk of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The accumulation of secondary lysosomes has been previously described in the thyroid of rats with a high iodine intake (five times the present dose and longer exposure to the iodine), and certainly these were evident in both AMD-and NaItreated rats (30). This finding is often explained by the accumulation of highly iodinated thyroglobulin which is resistant to proteolytic degradation (33,37,38). An increased number of lysosomes is also a well reported finding of AMD-induced ultrastructural change in other tissues (11,39,40).…”
Section: Discussionsupporting
confidence: 62%
“…The accumulation of secondary lysosomes has been previously described in the thyroid of rats with a high iodine intake (five times the present dose and longer exposure to the iodine), and certainly these were evident in both AMD-and NaItreated rats (30). This finding is often explained by the accumulation of highly iodinated thyroglobulin which is resistant to proteolytic degradation (33,37,38). An increased number of lysosomes is also a well reported finding of AMD-induced ultrastructural change in other tissues (11,39,40).…”
Section: Discussionsupporting
confidence: 62%
“…The group of Herzog (23,24) recently reported that macrophages in culture are capable of releasing T4 and T3 from Tg, a process requiring the internalization and then the proteolytic processing of Tg. Furthermore, these authors suggest that T3 and T4 produced by Kupffer cells of the liver could directly act on neighboring hepatocytes.…”
Section: Figurementioning
confidence: 99%
“…The thyroid hormone residues are released by early and limited alteration of the Tg structure [3]. Intensive Tg degradation is a delayed process, requiring several hours [4]. In spite of numerous reports on Tg proteolytic attacks by thyroid proteases [5][6][7][8][9], the physiological mechanisms for selective hormone release and sequential processing remain unclear.…”
Section: Introductionmentioning
confidence: 99%